Charles Kingsley, 1819-1875 - Thorp, Margaret Farrand (Princeton, NJ : Princeton University Press, 2015)
A biography of the distinguished novelist, poet, preacher and social reformer, who typifies the Victorian man as closely as the Good Queen herself typifies the Victorian woman.Originally published in 1937.The Princeton Legacy Library uses the latest print-on-demand technology to again make available previously out-of-print books from the distinguished backlist of Princeton University Press. These editions preserve the original texts of these important books while presenting them in durable paperback and hardcover editions. The goal of the Princeton Legacy Library is to vastly increase access to the rich scholarly heritage found in the thousands of books published by Princeton University Press since its founding in 1905.
Frontmatter -- PREFACE -- TABLE OF CONTENTS -- I. A BUGLE STRUNG SABLE -- II. "THE INSPIRATION OF MY LIFE BEFORE I MET YOU" -- III. "PAROXYSMS OF PAIN AND PETULANCE" -- IV. "AMAMUS" -- V. "VILLAGE SERMONS" -- VI. "IF IT SHALL DETER ONE YOUNG MAN" -- VII. "ESAU HAS A BIRTHRIGHT" -- VIII. "I AM A CHURCH OF ENGLAND PARSON-AND A CHARTIST" -- IX. "TAILOR AND POET" -- X. "THE THREE FISHERS" -- XI. "EMPLOYMENT FOR MY PEN" -- XII. "HOW TO TRAIN , NOT SCHOLARS BUT MEN" -- XIII. "EMERSONIAN ANYTHINGARIANISM" -- XIV. "A SANGUINARY BOOK" -- XV. "I SEE ONE WORK TO BE DONE ERE I DIE" -- XVI. "ALL OF ME WHICH WILL LAST" -- XVII. CHAPLAIN TO THE QUEEN AND TO THE PRINCE OF WALES -- XVIII. "THE ONLY COURSE FIT FOR A GENTLEMAN" -- XIX. "AS GREAT A TALKER AS ANY MAN IN ENGLAND" -- XX. "MUSCULAR CHRISTIANITY, A CLEVER EXPRESSION" -- XXI. "AT THE SERVICE OF THE GOOD CITIZENS OF CHESTER" -- XXII. "AT LAST" -- BIBLIOGRAPHY OF CHARLES KINGSLEY'S WORKS -- INDEX
Mode of access: Internet via World Wide Web.
In English.
Description based on online resource; title from PDF title page (publisher's Web site, viewed 08. Jul 2019)
Keywords: BIOGRAPHY & AUTOBIOGRAPHY / Religious